PELAKSANAAN TRIAS USAHA KESEHATAN SEKOLAH PADA TINGKAT SEKOLAH DASAR DI WILAYAH KECAMATAN TEMBALANG KOTA SEMARANG - Maryam Alifia Nurhayu; Zahroh Shaluhiyah; Ratih Indraswari (Jurnal Kesehatan Masyarakat (Undip), 2018)
Three main programs of the health school unit are composed of health education, health services, and healthy school environment coaching. The purpose of this study research was to analyze the implementation of three main programs of health school unit at elementary schools in Tembalang, Semarang. This research is an explanatory research with a cross-sectional design. This study took a sample by way of a total population of 33 schools. Data analysis in this study using univariate analysis, bivariate analysis using rank spearman and multivariate analysis using logistic regression. The results showed as much as 93.9% of schools do not have the ideal number of ideal doctors, 10% of the total students. Most schools stated that schools have not allocated special funds for three main programs of health school unit activities (57,6%). Only 15,2% of schools that provide UKS spaces are in accordance with the standard that has a minimum area of 12 square meters.  Analysis shows there is human resources relations with health education (p = 0.005; rs = 0,481). The variable funds there is no relationship with  health services (p = 0,099; rs = 0,292) and there is a relationship with the human resources with healthy school environment coaching (p = 0.003; rs = 0,506). There is the influence of the fund in the planning implementation of three main programs of health school unit (p-value = 0,026; odds ratio = 7,131). Recommended for the Community Health Care, UPTD Pendidikan and Governing Board Team of UKS to give training and coaching for implementing team of health school unit in school.